THE EFFECT OF COMPANY SIZE, BOARD OF COMMISSIONERS AND PROFITABILITY ON COMPANY VALUE - Wiwin Aminah; Dimas Farid Satria Nugraha (SEAN Institute, 2023)
One of the company's goals is to maximize its value. High corporate value indicates that the company can continue to run its business well and improve shareholder welfare. In the population of property and real estate subsector companies listed on the Indonesia Stock Exchange in 2017–2021, this study intends to determine the effect of total asset logs, board size, and ROA on PBV. Purposive sampling was the sampling technique used, and 50 companies were collected over a 5-year study period, resulting in 250 sample data. Panel data using eviews 12 is the data analysis method used in this study. The results of concurrent research show that profitability, the board of commissioners, and the size of the business all have an impact on the value of the company, but these effects are only partially beneficial. The size of the business also has a beneficial impact, as does the Board of Commissioners. According to the research findings, organizations should pay attention to their size (record total assets) as it has a beneficial impact on the value of their company. To grow the value of a company, businesses must be able to manage their assets effectively.